SPEAKING SKILL ABILITY IN HANDLING DIABETIC PATIENT IN 5TH SEMESTER NURSING STUDENTS OF STIKES BINA USADA BALI - Si Putu Agung Ayu Pertiwi Dewi; Ni Komang Purwaningsih (SPHOTA: Jurnal Linguistik dan Sastra, 2018)
ABSTRACT The increase in tourist visits to Bali has become a growing place in various sectors in Bali which have an impact on health support facilities in the form of international hospitals. In its supporting activities, English language is the main thing in this field health workers, especially nurses who are able to communicate in English are needed to achieve good communication with international patients who visit the hospital. English language proficiency possessed by nurse nurses is professional in providing care to patients where nurses must be able to explain nursing procedures, drug administration, appropriate handling that allows patients to speak accurately and correctly. The lack of ability of a student in English is a phenomenon that occurs due to various factors. This study raised the ability of 5th semester nursing students in Stikes Bina Usada Bali. In this study, Stikes Bina Usada Bali students majoring in Nursing were the object of research. This study aims to analyze the problems faced by students of Stikes Bina Usada Bali in the pronunciation and analysis of factors that influence the ability of English Language on students at Stikes Bina Usada Bali. Descriptive data was used to analyze data in this study. This study shows that nursing students at Stikes Bina Usada Bali experience problems in English as the influence of the mother tongue (main language of each student) and second language (Indonesian). Several factors also influence the ability of students to speak in the form of internal and external factors such as language components and content components and the environment during the learning process. Keywords: speaking ability, pronunciation, nurse, diabetes mellitus